Evolution of sustainability in global green building rating tools - Wen, Baohua; Musa, Siti Nurmaya; Onn, Chiu Chuen; Ramesh, Singh; Liang, Lihua; Wang, Wei (Elsevier, 2020)
Green building rating tools (GBRTs) are well-known and important instruments for assessing building sustainability. GBRTs constantly upgrade to meet rapid development, one of which is achieving a reasonable balance among the “three pillars” of sustainability, namely, environmental, social and economic sustainability. This study analyzes the changes and trends in the three sustainability pillars of GBRT and reinforces the previous GBRT longitudinal studies in terms of research sample, time span, equal terms, and research depth. Ten global GBRTs are selected by specific screening principles, and a unified criterion framework is presented to compare these selected GBRTs on equal terms. The changes of GBRTs are then analyzed on three levels, namely, categories, subcategories, and criteria. The results show that in the past three decades, there is a continuous decrease in the weight of the environmental category, an obvious increase in the weight of the social category and a little rise in the wight of the “economic” category. “Pollution,” “physical comfort,” and “flexibility” are identified as “sensitive criteria” of environmental, social, and economic categories, respectively, given their significant changes; they are also critical factors for the evolution of GBRT for the past three decades. © 2020 Elsevier Ltd